SMART IOT-BASED HEALTH AND LOCATION MONITORING SYSTEM FOR SOLDIER SECURITY (International Journal of Food and Nutritional Sciences, 2022)
These days, every country places a great premium on security. Land, water, and being the most powerful country are the targets of wars. The army, navy, and air force are the three professional uniformed services that make up a nation's armed forces. As the backbone of any armed force, soldiers typically die from a lack of access to medical care in an emergency. Additionally, troops participating in missions or special operations sometimes become disoriented on the battlefield and lose communication with the authorities. The system is divided into two units: the base station unit and the soldier's unit. As seen in the illustration below, a soldier's unit can be attached to their jacket. Major mobile is the base station unit. He or she can view every parameter on their phone. Additionally, this project is improved with NODE MCU and IOT technologies. Additionally, an LED lamp is used to establish indication at the local setup.